Morphological and molecular analyses reveal three new endemic species of the freshwater crab genus Buea Cumberlidge, Mvogo Ndongo, Clark & Daniels, 2019 (Crustacea: Brachyura: Potamonautidae) from a rainforest biodiversity hotspot in Cameroon, Central Africa. Issue 3 (25th May 2020) - Mvogo Ndongo, Pierre A; von Rintelen, Thomas; Tomedi-Tabi Eyango, Minette; Cumberlidge, Neil
Abstract: Three new species of the Cameroonian endemic freshwater crab genus Buea  Cumberlidge, Mvogo Ndongo, Clark & Daniels, 2019 are described. The new species were collected from protected areas in the Southwest region of Cameroon, the Korup and Bakossi National Parks and the Mt. Nlonako Ecological Reserve. These species are distinguished from each other and from the type species of the genus, Buea asylos (Cumberlidge, 1993 ), by a combination of morphological characters (carapace, thoracic sternum, chelipeds, and male first gonopod) and by partial sequences of three mitochondrial DNA genes (COI, 12S rRNA, and 16S rRNA). A phylogenetic analysis that included representatives of all other freshwater crab genera found in Cameroon recovered each of the new species as a well-supported distinct lineage. An identification key is also provided for the four species of Buea and the conservation status of the new species is discussed.